2020
DOI: 10.1002/brb3.1538
|View full text |Cite
|
Sign up to set email alerts
|

eNOS rs2070744 polymorphism might influence predisposition to hemorrhagic cerebral vascular diseases in East Asians: A meta‐analysis

Abstract: Introduction Endothelial nitric oxide synthase (eNOS) polymorphisms might influence predisposition to hemorrhagic cerebral vascular diseases, but the results of already published studies regarding relationship between eNOS polymorphisms and hemorrhagic cerebral vascular diseases were still controversial. Methods The authors performed this meta‐analysis to estimate relationship between eNOS polymorphisms and hemorrhagic cerebral vascular diseases in a larger pooled population by combing the results of already p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The generalized expression of i NOS in the CNS is pathological and is often observed during neurological diseases, such as multiple sclerosis, stroke, and Parkinson's disease [ 85 ]. In patients with AD, studies have shown that the number of i NOS-positive neurons significantly increases in the brain and is associated with neuronal damage [ 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…The generalized expression of i NOS in the CNS is pathological and is often observed during neurological diseases, such as multiple sclerosis, stroke, and Parkinson's disease [ 85 ]. In patients with AD, studies have shown that the number of i NOS-positive neurons significantly increases in the brain and is associated with neuronal damage [ 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 There is a significant relation (odds ratio >1, range 1.24-2.74) between NOS gene polymorphisms and the comorbidities associated to 2020-2021 deaths due to coronavirus disease 2019 (COVID-19). 13,17,18 The virus acts following two distinct stages. During stage 1, after the incubation period, the SARS-CoV-2 virus activates mild symptoms and protective immune responses.…”
mentioning
confidence: 99%
“…During stage 1, after the incubation period, the SARS-CoV-2 virus activates mild symptoms and protective immune responses. 18 During stage 2, a serious and damaging inflammatory response is activated. This affects mainly the lungs due to the triggering of a cytokines storm and the macrophage monocyte system.…”
mentioning
confidence: 99%
See 2 more Smart Citations